Acquisition of Hyperspectral Data with Colloidal Quantum Dots. Issue 11 (3rd October 2019) - Tang, Xin; Ackerman, Matthew M.; Guyot‐Sionnest, Philippe
Abstract: Hyperspectral sensors, combining the functions of photon detection with ultrahigh spectral resolution in a single device, have emerged as a new class of devices with significant potential for applications that rely on the input of optical information. Despite continued advancement, the widespread use of infrared hyperspectral sensors is still limited primarily due to the high cost associated with the growth and processing of epitaxial semiconductors, such as HgCdTe, InSb, and superlattices. Here, it is shown that colloidal quantum dots (CQDs) provide a promising route toward low‐cost, compact, and sensitive infrared hyperspectral sensors with tunable sensing ranges. In total, 64 narrowband channels with full‐width at half‐maxima down to ≈30 cm −1 can be realized by directly integrating CQDs sensors with a distributed Bragg mirror filter array. The results of high‐resolution spectra measurement with resolving power up to 180 and acquisition of a hyperspectral image cube in the short‐wave infrared range, benefitting from the fast (≈120 ns) and sensitive (>10 10 Jones) performance of the CQDs sensors, are experimentally demonstrated. Abstract : Hyperspectral sensors have emerged as a new class of devices with significant potential for applications that rely on the input of optical information. Colloidal quantum dots are shown to provide a promising route toward low‐cost, compact, and sensitive infrared hyperspectral sensors with tunable sensing ranges.